2021
DOI: 10.3390/polym13050762
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Sensor for Dengue Envelope Proteins Using Polyamidoamine Dendrimer Biopolymer-Based Nanocomposite Thin Film: Enhanced Sensitivity, Selectivity, and Recovery Studies

Abstract: This paper proposes a novel idea to enhance the sensitivity and selectivity of surface plasmon resonance (SPR) optical sensor for detection of dengue virus type-2 envelope proteins (DENV-2 E-proteins) using polyamidoamine (PAMAM) dendrimer biopolymer-based nanocomposite thin film. For this purpose, two ranges of DENV-2 E-protein concentrations, i.e., 0.000008–0.0001 nM and 0.00008–0.005 nM were evaluated, and the lowest detectable concentration was achieved at 0.00008 nM. The incorporation of PAMAM dendrimer-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 93 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is easy to improve signal sensitivity capable of detecting viruses by detecting envelope proteins. Several sensor studies using these envelope proteins have been reported [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is easy to improve signal sensitivity capable of detecting viruses by detecting envelope proteins. Several sensor studies using these envelope proteins have been reported [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%